DEVELOPMENT OF INITIAL ABILITY TEST INSTRUMENT BASED ON SCIENCE GENERIC SKILLS - Arta Elsa Ambarita; Ratu Evina Dibyantini; Ani Sutiani; Zainuddin Muchtar; Marudut Sinaga (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
This study aims to develop an initial ability test instrument based on science generic skills in the form of a scholastic test and develop a final chemistry evaluation test instrument in the topic of thermochemistry as well as find out the validity of the content and construction validity of the instrument. Research and development research, with a 4D development model consisting of 4 main stages, namely: Define, Design, Develop and Disseminate, due to time constraints this research was only up to develop. The results of the content validity test by experts obtained an average percentage of material aspects, namely 87.08%, construction aspects, namely 90.41%, language aspects, 92.5% and additional rules, 96.67%, so the question instrument is suitable for use. Based on the construction validation test data, it was found that of the 20 questions on the scholastic potential test tested, there were 19 questions that were valid and considered appropriate, while 1 other item was invalid, while of the 20 questions on the chemistry test tested, there were 17 questions that were valid and considered feasible, leaving 3 questions other invalid. For further research, it is hoped that this instrument can be implemented.